Development of Javanese-Sundanese Culture-Based Educational Comic Media (JASUN) to Increase Tolerance in Multicultural Education in Elementary School Students - Didik Tri Setiyoko; Eva Banowati; Agustinus Sugeng Priyanto; Arif Purnomo (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background:  Indonesia's cultural diversity constitutes vital social capital that must be nurtured through education from an early age. Elementary school is a strategic level for instilling tolerance, mutual respect, cooperation, and appreciation of diversity. However, multicultural education in Indonesian schools still faces obstacles such as limited contextual learning media, memorization-oriented teaching, and minimal integration of local cultural values. Objective:  This study aims to develop and test the effectiveness of a Javanese-Sundanese culture-based educational comic (JASUN) as a multicultural learning medium for elementary school students. Methods:  This study used the Research and Development (R&D) method following Reeves’ Design-Based Research (DBR) model, combined with a quasi-experimental pretest-posttest control-group design. Data were collected through observation, interviews, questionnaires, and tests, then analyzed descriptively and inferentially using validity, reliability, normality, homogeneity, and independent-samples t-tests. Results:  The JASUN comic was declared valid for use by media, content, and language experts (see Table 9), the tolerance-attitude instrument showed strong reliability (Cronbach's Alpha = 0.835), and the experimental class's tolerance score rose from 29.57 to 34.80, significantly higher than the control class (t = 5.008, p = 0.000 < 0.05), confirming that the comic effectively improved students' tolerance attitudes. Conclusion:  These findings provide conceptual, methodological, and empirical contributions to the development of culturally responsive learning media and to strengthening multicultural education practice at the elementary school level.